1980
DOI: 10.3109/03009738009179181
|View full text |Cite
|
Sign up to set email alerts
|

Urinary pH and the Indwelling Catheter

Abstract: The pH of the urine within a blocked indwelling catheter was significantly higher than the pH of the first urine portion from the new catheter. This observation suggests that the urinary pH was changed in an alkaline direction within the indwelling catheter, probably due to the production of ammonia induced by urease from Proteus strains. This pH gradient could only be demonstrated under conditions where the circadian pH variations of the urine within the individual could be neglected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Most of this rise occurs within a period of 2 h, and the pH remains approximately constant for the remaining seven days of the test. The final pH value is within the range of pH values of 6.5-10 which have been recorded for naturally infected urine in catheters (Norberg et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Most of this rise occurs within a period of 2 h, and the pH remains approximately constant for the remaining seven days of the test. The final pH value is within the range of pH values of 6.5-10 which have been recorded for naturally infected urine in catheters (Norberg et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of urease-producing organisms in catheter encrustation, which may lead to obstruction, has been demonstrated by several groups. For example, Norberg et al (174) isolated Proteuts strains from 13 of 15 patients with catheters removed because of obstruction; however, the frequency of Protelus isolation was not reported for catheters removed for other reasons. Burns and Gauthier (29) demonstrated that catheter encrustation in five patients with long-term indwelling catheters could be significantly reduced by the administration of acetohydroxamic acid.…”
Section: Role Of Urease In Pathogenesismentioning
confidence: 99%
“…Whether the sensor is measuring pHv or the pH of the biofilm is not certain, but the time between sensor indication and blockage would suggest that the relationship between pH and the encrustation process may be too complex or capricious for pHv to be a single proxy measure for impending blockage. Several studies have investigated the relationship between pHv, the presence of urease‐producing micro‐organisms and propensity for catheters to encrust . Hedelin et al.…”
Section: Discussionmentioning
confidence: 99%